2009
DOI: 10.1074/jbc.m806962200
|View full text |Cite
|
Sign up to set email alerts
|

p38 MAPK Is an Early Determinant of Promiscuous Smad2/3 Signaling in the Aortas of Fibrillin-1 (Fbn1)-null Mice

Abstract: Excessive transforming growth factor-␤ (TGF-␤) signaling characterizes the progression of aortic aneurysm in mouse models of Marfan syndrome, a systemic disorder of the connective tissue that is caused by mutations in the gene encoding the extracellular matrix protein fibrillin-1. Fibrillin-1 mutations are believed to promote abnormal Smad2/3 signaling by impairing the sequestration of latent TGF-␤ complexes into the extracellular matrix. Here we report that promiscuous Smad2/3 signaling is the cell-autonomous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
77
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 94 publications
(83 citation statements)
references
References 40 publications
(56 reference statements)
6
77
0
Order By: Relevance
“…Our results indicate that endoglin haploinsufficiency has a significant impact on EC junctional organization and function, and are consistent with an increase in TGFb-mediated Smad2/3 phosphorylation in Eng+/2 EC (Fig. 8D) as previously reported by downregulation of VE-cadherin (Rudini et al, 2008) and/or activation of P38 MAPK (Carta et al, 2009;Mu et al, 2012).…”
Section: Discussionsupporting
confidence: 75%
“…Our results indicate that endoglin haploinsufficiency has a significant impact on EC junctional organization and function, and are consistent with an increase in TGFb-mediated Smad2/3 phosphorylation in Eng+/2 EC (Fig. 8D) as previously reported by downregulation of VE-cadherin (Rudini et al, 2008) and/or activation of P38 MAPK (Carta et al, 2009;Mu et al, 2012).…”
Section: Discussionsupporting
confidence: 75%
“…A series of studies has reported paradoxical upregulation of TGF- signaling in aortic tissues of patients with mutations in the TGFBR2 kinase domain, as shown by increased levels of nuclear phosphorylated Smad, abundance of TGF- and expression of TGF- target genes (Carta et al, 2009;Gomez et al, 2009;Loeys et al, 2005). The basis of this observation, however, has not been elucidated to date.…”
Section: Discussionmentioning
confidence: 89%
“…So far, all of these facts indicate a very finely tuned inflammatory process in human aortic aneurysms and therefore the recently postulated prognostic value for phosphorylation of c-kit and downstream targets in aneurysm formation fits well in this concept [20]. In this context, recent studies reported that the inhibition of cytokine IL-1 attenuates experimental development of aortic aneurysm [21], as well as activation of TGF-signalling [22]. Future studies should address the exact characterization and cellular imaging of the inflammatory cells, that is, T-cells, macrophage subpopulations, and so forth, in order to better understand their specific contribution during development of human aneurysms.…”
Section: Discussionmentioning
confidence: 95%